A critical review on the ecotoxicity of heavy metal on multispecies in global context: A bibliometric analysis - Gogoi, Bhagyudoy; Acharjee, Shiva Aley; Bharali, Pranjal; Sorhie, Viphrezolie; Walling, Bendangtula; Alemtoshi (Environmental research, 2024)
Heavy metals (HMs) have become a significant concern in the current era, with deleterious effects on diverse living organisms when exposed beyond threshold concentrations. Both nature and human beings have been constantly casting out HMs into environmental matrices through various activities. Innumerable cases of threatened diseases such as cancer, respiratory ailments, reproductive defects, skin diseases, and several others have been a cause of significant concern for humans as the number of instances has been increasing with each decade. HMs migrates via several pathways to infiltrate biological organisms and amass within them. Even though numerous treatment approaches are available for remediating HM pollution, however, they are expensive, along with other setbacks. Due to such constraints, combating HM contamination requires environmentally conscious strategies like bioremediation, which employs an array of biological systems to remove HMs from the environment. Nonetheless, to address the current global HM pollution situation, it is critical to comprehend not only how these hazardous HMs cause toxicity in various living organisms but also the knowledge gaps that currently exist concerning the subject of HM ecotoxicity. In the present investigation, data was extracted from Google Scholar using software program called Harzing's Publish or Perish. The collected information has been subsequently displayed as a network file using the VOSViewer software tool. Thus, the current review presents a significant insight with the inclusion of a readily accessible bibliometric analysis to comprehend the present status of HMs research, global research trends, existing knowledge discrepancies, and research challenges. Further, it also provides an in-depth review of HMs ecotoxicity, with a focus on arsenic (As), cadmium (Cd), and lead (Pb). Thus, as indicated by the bibliometric study, the present review will assist future investigators studying HMs ecotoxicity by providing baseline data concerning a wide range of living organisms and by addressing research gaps. [Display omitted]